Uma opção para administrar empresas publicas: o contrato de gestão entre o governo do Brasil e a Companhia Vale do Rio Doce - Ardila Guzman, Elsa Maria (1994)
In order to face negatives effects of statization and to assure some level of success in lhe liberal process of economic growth, Brazilian Govenment has developed administrative reforms, adopted privatizations measures and financial programs, and implemented new decision making methods, like strategies to modernize the governmental management. The Brazilian enterprise, Companhia Vale Do Rio Doce - CVRD, a worlwide successfull company. was the first to participate in a Contract Managemem w1th the (Government in june 1991. Its purpose was: 1) to improve lhe relationship betwen the assignity parts 2) to give high operational autonomy to the enterprise, in order to increase its competitive and proouctivily leveis ano, 3) lo improve the Governmenl control functions. Like other countries in the world, which implemented Contract Programs. the Hrazilian practice~ althought incipient~ has demostrated succesfuli ouicome. The CVRD, not nnly, has riched the necessary autonomy lo adopt a single adminislralion in the entire enterprise. but has also. improved its managment, becoming better understood by the fiscal organisms. Therefore, llu: Governmenl, officialized a new system of public enterprise rnanagement, based on Contract Prograrns. This system opencd an important precedent and demostrated a sucessfull example of the managment contracts in the puh1ic enterprises as an instrument oi' objetive contro1.